2013
DOI: 10.1080/19440049.2013.814169
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of dioxins, furans and dioxin-like PCBs in Austria

Abstract: Human exposure to polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and dioxin-like PCBs (dl-PCBs) should be assessed regularly. In order to evaluate the contamination levels in various food products on the Austrian market and to assess the dietary exposure of the Austrian population for the first time, a national monitoring programme was conducted from 2005 to 2011. The 235 food products comprised meat, poultry, game and offal, fish and fish products, milk and dairy products, eggs, animal fats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In China, a total diet study was also conducted in Hong Kong in 2010 (FEHD, 2011), the mean exposure of adult population, 0.73 pg TEQ kg À1 bw day À1 (WHO-TEF of 1998), was concordant with average exposure of Chinese adult population in present study. Moreover, other methods, including market basket study, and monitoring program, were also applied to evaluate the dietary intake for residents in many countries (Arisawa et al, 2008;Perelló et al, 2010;Marin et al, 2011;Törnkvist et al, 2011;Rauscher-Gabernig et al, 2013;Husain et al, 2014). Some studies have indicated that cooking process might be a source of PCDD/Fs and dl-PCBs Wu et al, 2011).…”
Section: Dietary Intake Estimationmentioning
confidence: 99%
“…In China, a total diet study was also conducted in Hong Kong in 2010 (FEHD, 2011), the mean exposure of adult population, 0.73 pg TEQ kg À1 bw day À1 (WHO-TEF of 1998), was concordant with average exposure of Chinese adult population in present study. Moreover, other methods, including market basket study, and monitoring program, were also applied to evaluate the dietary intake for residents in many countries (Arisawa et al, 2008;Perelló et al, 2010;Marin et al, 2011;Törnkvist et al, 2011;Rauscher-Gabernig et al, 2013;Husain et al, 2014). Some studies have indicated that cooking process might be a source of PCDD/Fs and dl-PCBs Wu et al, 2011).…”
Section: Dietary Intake Estimationmentioning
confidence: 99%
“…In addition to previously published results for PCDD/Fs and dl-PCBs (Rauscher-Gabernig et al, 2013), the aim of the present study was to estimate the dietary exposure to R 6 PCBs in order to assess the risk for different Austrian population groups. The exposures were calculated by combining concentrations found within this study with national consumption data (Elmadfa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PCP), where birds are kept for the family's and neighbour's own use (19). High concentrations of these compounds have been noted in many European countries, including Poland, and in other continents (12,20,21,24). In Vietnam, despite the wars, which ended 40 years ago, exceptionally high concentrations have been noted (248 pg WHO-TEQ/g of fat for PCDD/F and 249.1 pg WHO-TEQ/g of fat for the sum of PCDD/Fs and dl-PCBs).…”
Section: Discussionmentioning
confidence: 99%